A Review on Extraction Techniques and Its Future Applications in Industry. Issue 4 (1st March 2021) - Geow, Chin Hong; Tan, Mei Ching; Yeap, Swee Pin; Chin, Nyuk Ling
Abstract: Extraction is a mandatory process for most of the industries, especially in the food processing industry to obtain the targeted compounds from various sources such as plant or seed samples. This review paper provides information about various extraction techniques that are normally used in the edible oil extraction industry. Five extraction techniques are presented in this paper. Among all the techniques presented in this paper, pressing and solvent extraction methods are considered as traditional techniques while supercritical fluid extraction, microwave assisted extraction, and ultrasound assisted extractions are considered as advanced techniques. Both advantages and disadvantages of supercritical fluid extraction, microwave assisted and ultrasound assisted extractions are discussed. Furthermore, the parameters that would affect the output of each technique are included in each section. Nowadays, research is going on to further enhance the extraction method to obtain a higher extraction yield or increase the quality of the extraction product. The enhancement can be either combining two or more extraction techniques into one complete process or modifying the available technique alone. Therefore, the theoretical knowledge provided in this review will be useful for future researchers who are interested in enhancing the extraction techniques. Practical Applications : Extraction is a mandatory process in edible oil extraction industry. Extraction industry is always looking for a process which is high efficiency and low extraction cost. Therefore, various advanced techniques or treatments are applied to optimize the oil yield and shorten the extraction time. This paper provides a review on various techniques by summarizing both advantages and disadvantages of each technique. The information can be very useful for improving the current extraction technique to further optimize the oil yield or enhance the quality of oil. Abstract : In this review article, several types of extraction methods are presented. The article provides information such as advantages and disadvantages of each extraction method. The article is very useful for the researchers who have the interest in developing or enhancing the extraction technique in order to achieve higher yield of extraction.